Двухмодовое возбуждение ГДИ с локальной магнитостатической неоднородностью - Одаренко, Е. Н. (ХГУ им. А.М. Горького, 1992)
The effect of the localized magnetic nonuniformity position on the two-mode excitation conditions is investigated. The rf field amplitude distributions of modes are represented by the Gauss-Hermite functions.
Keywords: генератор дифракционного излучения; неоднородное фокусирующее поле; моды открытого резонатора; двухмодовое возбуждение